1996
DOI: 10.1108/00346659610108966
|View full text |Cite
|
Sign up to set email alerts
|

High pressure food processing

Abstract: Discusses the use of high pressure in the processing, packaging and shelf life of food products. Describes the effects of high pressure on food microbiology, chemistry and structure. Suggests there are commercial opportunities for new products using pressure packaging as the flavours and colours of fresh food are maintained with minimal processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 7 publications
(6 reference statements)
0
6
0
2
Order By: Relevance
“…the vessel is sealed and the vessel filled with pressure transmitting agent. The high pressure is usually carried out with water as a hydraulic fluid to facilitate the operation and compatibility with food materials (17). the basis for applying high pressure to foods is to compress the water surrounding the food.…”
Section: High Pressure Equipmentmentioning
confidence: 99%
See 1 more Smart Citation
“…the vessel is sealed and the vessel filled with pressure transmitting agent. The high pressure is usually carried out with water as a hydraulic fluid to facilitate the operation and compatibility with food materials (17). the basis for applying high pressure to foods is to compress the water surrounding the food.…”
Section: High Pressure Equipmentmentioning
confidence: 99%
“…Some authors showed that the pressure resistance of microbial organisms is maximal at temperature [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] o C and decreases significantly at higher or lower temperature (10,11,12).…”
Section: High Pressure Processing and Microbial Inactivationmentioning
confidence: 99%
“…A potencialidade do uso da alta-pressão como método para processar e conservar alimentos já era conhecida e estudada desde 1899 por HITE, mas ficou praticamente adormecida até a década de 80, quando estudos a este respeito foram intensificados (HOOVER et al, 1989;MERTENS, 1992;KNORR, 1993;ARROYO & PRESTAMO, 1996;EARNSHAW, 1996).…”
Section: Tecnologia De Alta-pressãounclassified
“…O princípio de destruição e/ou inativação de microorganismos deteriorantes baseia-se no rompimento de membranas e organelas celulares e desnaturação de proteínas componentes das membranas lipoprotéicas, bem como das enzimas microbianas. A desnaturação protéica é também responsável pela inativação de enzimas deteriorantes originárias do próprio alimento (CHEFTEL, 1995;EARNSHAW, 1996;ROSENTHAL & SILVA, 1997;ROSENTHAL et al, 1999).…”
Section: Tecnologia De Alta-pressãounclassified
“…However, when these technologies are applied singly, their effectiveness is not as pronounced compared to when they are combined. Combination of these technologies, termed hurdle processing, and their synergistic effects have been demonstrated (Farr 1990;Earnshaw 1996;Ross et al 2003;Char et al 2010).…”
Section: Introductionmentioning
confidence: 99%